An Examination of the Relationship Between the Functional Movement Screen, Landing Error Scoring System, and 3D Kinematic Data During a Drop Jump Task. Issue 11 (November 2021) - Everard, Eoin; Lyons, Mark; Harrison, Andrew J.
Abstract : Abstract: Everard, E, Lyons, M, and Harrison, AJ. An examination of the relationship between the functional movement screen, landing error scoring system and 3D kinematic data during a drop jump task. J Strength Cond Res 35(11): 3012–3020, 2021—Tests such as the Functional Movement Screen (FMS) and Landing Error Scoring System (LESS) have become an established component of preparticipation screening. Despite their practical use, there is a lack of empirical evidence examining their relationship to established assessments of movement, such as 3D kinematics of a drop jump. Fifty-two male collegiate athletes undertook the LESS, FMS, and a drop jump where 3D lower-limb kinematic variables were assessed. Spearman correlations were conducted to examine the relationship between LESS, FMS, and drop-jump 3D kinematic variables. A series of independent t -tests examined differences in hip and knee kinematic variables in acceptable and poor FMS and LESS groups as determined by established cut-off scores. Landing Error Scoring System scores had significant moderate correlations with most kinematic variables ( r = 0.35–0.64; p < 0.01). Subjects with poor LESS scores displayed significantly worse lower-limb kinematics compared with their high-scoring counterparts (effect size = 1.99–2.76, large effect). There were significant moderate correlations with maximal hip and knee flexion ( r = 0.46 and 0.39 respectively; p < 0.01) and small or nonsignificant correlations between all other kinematic variables and FMS scores. Hip flexion and knee valgus at maximal displacement were the only kinematic variables significantly different between FMS groups (ES = 0.70–0.72, small-to-moderate effect). The results confirm limitations in the ability of the FMS to distinguish between groups for landing biomechanics.